Surgical lung cancer patients' views about smoking and support to quit after diagnosis: a qualitative study - Farley, A; Aveyard, P; Kerr, A; Naidu, B; Dowswell, G (Springer US, 2015)
Evidence suggests that quitting smoking improves symptoms as well as disease-related mortality for cancer patients. However, smoking cessation support is typically not well integrated into routine cancer care even in the case of lung cancer.. We explored surgical lung cancer patients' views about smoking and about their preferences for support to help them to quit.We conducted semi-structured, qualitative interviews with 22 surgical lung cancer patients with a smoking history, after treatment with surgery. Data were analysed using the framework approach.Although diagnosis promoted a successful quit attempt in some, others continued smoking or relapsed after a quit attempt. Most participants wished they were a non-smoker but, in conflict with this, also felt that smoking was enjoyable, helped with psychological coping or had some health benefits. Some also demonstrated a fatalist attitude towards the potential detrimental health effects. However, all participants felt that it was important for health professionals to address smoking and some wanted cessation support although it was often not provided. Participants wanted support to start as early as possible and to continue for the first weeks after discharge.Surgical lung cancer patients often stop smoking during hospitalisation, and many want to remain quit but relapse shortly after discharge. Although it is often not provided, many patients want to be offered support to help them quit.Surveys suggest that clinicians believe that addressing smoking will be difficult and/or unwanted. However, these findings suggest that surgical lung cancer patients would tolerate, and most would prefer, integration of smoking cessation support into routine cancer care.